2015
DOI: 10.1016/j.cmi.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Predicting carriage with extended-spectrum beta-lactamase-producing bacteria at hospital admission: a cross-sectional study

Abstract: The prevalence of patients colonized with extended-spectrum beta-lactamase (ESBL)-producing bacteria increases, especially in long-term-care facilities (LTCFs). Identification of ESBL carriers at hospital admission is relevant for infection control measures and antibiotic therapy for nosocomial infections. We aimed to develop a prediction rule for ESBL carriage at hospital admission for patients admitted from home and LTCFs, and to quantify incidences of nosocomial infections caused by ESBL-producing bacteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 23 publications
7
37
1
Order By: Relevance
“…Our prevalence of intestinal carriers at admission is virtually the same as that found by a Dutch study published recently, which was 7.9% in patients coming from their homes and 8.6% in patients coming from long-term care facilities, a distinction not made in our research 21. Studies in three different areas in Spain (Madrid, Barcelona and Zaragoza) show that the prevalence of carriers has increased in the last few years, reaching rates ranging from 5.5% and 8.1% in 2002 and 2004 respectively, as in our study findings 11 13 16.…”
Section: Discussionsupporting
confidence: 88%
“…Our prevalence of intestinal carriers at admission is virtually the same as that found by a Dutch study published recently, which was 7.9% in patients coming from their homes and 8.6% in patients coming from long-term care facilities, a distinction not made in our research 21. Studies in three different areas in Spain (Madrid, Barcelona and Zaragoza) show that the prevalence of carriers has increased in the last few years, reaching rates ranging from 5.5% and 8.1% in 2002 and 2004 respectively, as in our study findings 11 13 16.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of ESBL among E. coli and K. pneumoniae in our study (3.6%) was comparable with the national data. Other studies reported prevalences ranging from 4.5 to 19.1% [18][19][20][21][22][23][24][25]. It should be noted, however, that these other studies have included populations that are not comparable with our patient population.…”
Section: Discussionmentioning
confidence: 74%
“…In these studies, faecal samples were examined. Paltansing et al [24] included travellers and rectal swabs, whereof one isolate was Citrobacter freundii, and Platteel et al [25] analysed perianal and faeces swabs from patients admitted to the hospital. The study population of Star-SHL is most comparable with the population of NethMap, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of UK surfers, Leonard et al 5 found that 1.5 per cent of a non-surfing, control population were colonised by E coli -bearing bla CTX-M compared with 6.3 per cent of UK surfers. Intestinal colonisation with ESBL-producing bacteria before hospital admission is associated with increased risk of nosocomial infection 6. Patients with infections caused by ESBL-producing bacteria and carriers of these organisms represent a source of resistance and can be responsible for nosocomial and community transmission 7.…”
Section: Introductionmentioning
confidence: 99%